2009
DOI: 10.5650/jos.58.313
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged Swimming Exercise Does Not Affect Contents and Fatty Acids Composition of Rat Muscle Triacylglycerol

Abstract: The present study investigated whether or not muscle triacylglycerol (MTG) contributed as a main energy source and MTG level and utilized fatty acid (FA) composition decreased during a 4-hour swimming exercise in rats fed a normal diet or a high-fat diet (HFD). Sixty male Wistar rats aged 5 weeks were fed a normal diet (CE-2, n = 25, experiment A) or HFD (n = 35, experiment B) for 22 days. On the final day, rats in both experiments were killed either without exercise or 1, 2, 3, or 4 hours after beginning the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2012
2012
2014
2014

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 45 publications
(58 reference statements)
0
2
0
1
Order By: Relevance
“…In male Wistar rats fed with normal diet and submitted to swimming training with different duration, it was identified that glycemia was higher in the groups which swam for two to four hours, compared with the animals from the group which did not exercise 21 . In male Wistar rats fed with carbohydrate-rich diet or fat-rich diet and whose blood collections were performed pre and post-swimming exercise, it was observed that the serum glucose concentration was not different among the experimental groups in the post-exercise 22 .…”
Section: Discussionmentioning
confidence: 99%
“…In male Wistar rats fed with normal diet and submitted to swimming training with different duration, it was identified that glycemia was higher in the groups which swam for two to four hours, compared with the animals from the group which did not exercise 21 . In male Wistar rats fed with carbohydrate-rich diet or fat-rich diet and whose blood collections were performed pre and post-swimming exercise, it was observed that the serum glucose concentration was not different among the experimental groups in the post-exercise 22 .…”
Section: Discussionmentioning
confidence: 99%
“…In a study on male Wistar rats fed a high-carbohydrate or high-fat diet in which blood samples were collected pre-and post-swimming exercise, serum glucose concentration only differed between the pre-and post-exercise experimental groups 20 , i.e., between rested animals and animals submitted to 1 h of swimming. When male Wistar rats fed a normal diet and submitted to swimming training of different durations were studied, the groups swimming for 2 and 4 h exhibited higher glucose levels than untrained animals 21 . In another study, no difference in glucose levels was observed between adult male Wistar rats submitted to 4 weeks of swimming exercise with an overload of 5% of body weight and the sedentary group 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Em relação à glicemia a literatura demonstra que, em ratos machos Wistar alimentados com dieta normal e submetidos a treinamento de natação com diferentes durações se identifi cou que a glicemia foi maior nos grupos que nadaram por duas e quatro horas, comparados aos animais do grupo que não se exercitou (OCHIAI & MATSUO, 2009a). Ratos Wistar machos alimentados com dieta rica em carboidratos ou dieta rica em gorduras e cujas coletas sanguíneas foram realizadas pré e pós-exercício de natação se observou que a concentração de glicose sérica não diferiu entre os grupos experimentais no pós-exercício (OCHIAI & MATSUO, 2009b).…”
Section: Contagem De Leucócitos Circulantes (Nº De Células/mm 3 )unclassified